ANOMALIAS CONGÊNITAS DE VEIA CAVA INFERIOR E SUAS IMPLICAÇÕES PARA TRANSPLANTE DE FÍGADO: UMA REVISÃO INTEGRATIVA DA LITERATURA - Fonseca Neto, Olival Cirilo Lucena da; Nascimento, Maria Eduarda de Freitas Mesquita do (Brazilian Journal of Transplantation, 2020)
Introduction: The Vena Cava formation is a complex embryological process, and rare malformations may occur during it, such as absence, duplication, situs inversus, presence of membrane, and left vena cava. Generally, these malformations do not cause physiological or clinical implications. However, such anomalies have important surgical implications mainly in urological, vascular and transplant surgeries, demanding technical modifications and attention to avoid iatrogenic lesions. Purpose: This paper aims to present the most important vena cava anomalies and its implications to liver transplant. Method: Integrative review of literature performed by searching on the PubMed, Scielo and Lilacs databases, having articles selected, which were published in the last five years (2016-2020), after applying the inclusion and exclusion criteria defined by the authors. Conclusion: For the implications of the inferior vena cava anomalies in the organ harvesting and transplant, it is indispensable that surgeons examine the vena cava anatomy, being capable of identifying its malformations, as well as managing them by performing technical adaptations whenever required, without contraindicating liver transplant due to the presence of malformations in the donor or receptor vena cava.